2018
DOI: 10.1038/s41564-018-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular replication of Streptococcus pneumoniae inside splenic macrophages serves as a reservoir for septicaemia

Abstract: Bacterial septicaemia is a major cause of mortality, but its pathogenesis remains poorly understood. In experimental pneumococcal murine intravenous infection, an initial reduction of bacteria in the blood is followed hours later by a fatal septicaemia. These events represent a population bottleneck driven by efficient clearance of pneumococci by splenic macrophages and neutrophils, but as we show in this study, accompanied by occasional intracellular replication of bacteria that are taken up by a subset of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
157
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(172 citation statements)
references
References 62 publications
15
157
0
Order By: Relevance
“…However, this raises the important question of how the pneumococcus causes septicemia despite clearance from the bloodstream by splenic macrophages. Ercoli et al () investigated this phenomenon and found that CD169 + splenic macrophages serve as a reservoir for intracellular replication of internalised pneumococci. Using a 1:1 inoculation of mice with D39 strains expressing green or red fluorescent proteins, they showed that bacterial foci within the spleen consisted entirely of single labelled bacteria.…”
Section: Replication Within the Spleenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this raises the important question of how the pneumococcus causes septicemia despite clearance from the bloodstream by splenic macrophages. Ercoli et al () investigated this phenomenon and found that CD169 + splenic macrophages serve as a reservoir for intracellular replication of internalised pneumococci. Using a 1:1 inoculation of mice with D39 strains expressing green or red fluorescent proteins, they showed that bacterial foci within the spleen consisted entirely of single labelled bacteria.…”
Section: Replication Within the Spleenmentioning
confidence: 99%
“…However, this raises the important question of how the pneumococcus causes septicemia despite clearance from the bloodstream by splenic macrophages. Ercoli et al (2018) investigated this phenomenon and found that CD169 + splenic macrophages serve as a reservoir for intracellular replication of internalised pneumococci.…”
Section: Replication Within the Spleenmentioning
confidence: 99%
“…Gerlini and Colleagues () demonstrated that this bottleneck can be extremely narrow (10–100 cells), and in some cases can even result in clonal expansion from a single surviving bacterium. Very recently, Ercoli and Colleagues () utilised microscopy to connect this systemic bottleneck with permissiveness for pneumococcal replication in a subset of CD169+ splenic macrophages. Infection and bacterial replication within these cells was essential for disease, as evidenced by survival of mice treated with an anti‐CD169 monoclonal antibody, however, infection of these cells did not impose selection for a particular genotype but was instead stochastic for isogenic genotypes.…”
Section: Selective and Non‐selective Bottlenecks Influence Bacterial mentioning
confidence: 99%
“… —Immunogenicity of the capsular serotype of the pneumococcus, magnitude of bacteraemia and impact on rate of clearance of the pathogen —Propensity to produce pneumolysin and intramyocardial biofilm, enabling persistence in cardiomyocytes, cardiac fibroblasts and macrophages ; —Propensity to survive intracellularly in CD169 + splenic macrophages, M2‐polarized macrophages and dendritic cells ; —Persistence of pneumococcal antigens in pathogen‐derived extracellular vesicles ; —Persistence due to capsular switching . …”
Section: Persistent Inflammation Following Clinical Recovery From Pnementioning
confidence: 99%